2017
DOI: 10.1111/pce.13064
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis U‐box E3 ubiquitin ligase PUB30 negatively regulates salt tolerance by facilitating BRI1 kinase inhibitor 1 (BKI1) degradation

Abstract: The Arabidopsis U-box E3 ubiquitin ligases play an important role in the ubiquitin/26S proteasome-mediated protein degradation pathway. Recently, PUB30 has been reported to participate in the salt stress response during seed germination stage in abscisic acid (ABA)-independent manner, but the molecular mechanism remains to be elucidated. Here, we displayed that the pub30 mutant was more tolerant to salt stress during seed germination, whereas the mutant of its closest homologue PUB31 showed mild sensitivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…In this study, 9-cis-epoxycarotenoid dioxygenase NCED9 (BRADI1G13760, Log2fc = 1.1422), a fundamental enzyme in the biosynthesis of ABA, was upregulated. Based on the transcriptome data of B. distachyon under salt stress, our findings were consistent with the previous data which indicated that the genes related to BRs signal transduction, such as BKI1 (BRADI4G32220, Log2fc = 1.7916), BSK2 (BRADI3G33950, Log2fc = 3.3028), and BZR1 (BRADI1G23550, Log2fc = 3.8252), are upregulated ( Figure S2) [71][72][73].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 9-cis-epoxycarotenoid dioxygenase NCED9 (BRADI1G13760, Log2fc = 1.1422), a fundamental enzyme in the biosynthesis of ABA, was upregulated. Based on the transcriptome data of B. distachyon under salt stress, our findings were consistent with the previous data which indicated that the genes related to BRs signal transduction, such as BKI1 (BRADI4G32220, Log2fc = 1.7916), BSK2 (BRADI3G33950, Log2fc = 3.3028), and BZR1 (BRADI1G23550, Log2fc = 3.8252), are upregulated ( Figure S2) [71][72][73].…”
Section: Discussionsupporting
confidence: 91%
“…Both tissue expression maps suggest that PUB30 is expressed globally (Klepikova et al, 2016; Winter et al, 2007). PUB30 has a described function in inhibiting the salt stress response (Hwang et al, 2015; Zhang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…PUB48 and PUB30 are involved in stress responses. PUB30 is involved in the response to high salt conditions, and mutants exhibit reduced salt tolerance (Hwang et al, 2015; Zhang et al, 2017). Perturbations in the circadian clock can lead to altered salt stress response, so it is possible that alterations in the circadian clock of the pub30 mutants similar to what we observe with the PUB30 decoy leads to the observed salt stress phenotype (Kim et al, 2013; Nakamichi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These included the non-ATPase regulatory subunit RPN7 which forms part of the 19S regulatory particle, as well as the armadillo-repeat superfamily protein At3g15180 that contains a domain (InterPro:IPR019538) found in proteasomal chaperones involved in assembly of the proteasome [40]. Moreover, we identified three E3 ubiquitin ligases: ( i ) the F-box protein EBF2 which is part of an SCF EBF1/2 ubiquitin ligase that targets the ethylene-responsive transcription factor EIN3 for proteasome-mediated degradation [41, 42]; ( ii ) the U-box type E3 ligase PUB23 that has been implicated in plant immunity, interacts with and ubiquitinates the 19S proteasome regulatory particle subunit RPN6 [43, 44]; and ( iii ) the U-box type E3 ligase PUB31 that is involved in abiotic stress tolerance [45]. Finally, UPL3 was found to interact with UBP12, a deubiquitinase of the proteasome pathway that negatively regulates immunity [46].…”
Section: Resultsmentioning
confidence: 99%